Impact of albumin levels on clinical outcomes in children underwent abdominal surgery - Rismala Dewi; Freddy Guntur Mangapul Silitonga; Irawan Mangunatmadja (Indonesian Pediatric Society, 2020)
Background Patients underwent abdominal surgery and had hypoalbuminemia were at risk of post-operative complications. The prognostic role of albumin levels in children with abdominal surgery remains unclear. Objective To investigate the impact of albumin levels on clinical outcomes related to the complications in children with abdominal surgery. Methods This was a retrospective cohort study on children aged 29 days to 18 years, who underwent abdominal surgery, had serum albumin levels measured at pre-operative and within 48 hours post-operatively, and hospitalized in Paediatric Intensive Care Unit of Dr. Cipto Mangunkusumo Hospital, Indonesia. The primary outcomes were post-operative complications (sepsis, surgical site infection, shock), length of stay in PICU, dehiscence, relaparotomy, and postoperative mortality. Results This study recruited a total of 201 children. Pre- and post-operative serum albumin levels of ≤ 3.00 g/dL were found in 15.4% and 51.2%, respectively. Pre- and post-operative serum albumin levels of ≤ 3.00 g/dL were associated with higher risk of post-operative sepsis (RR 3.4; 95%CI 1.54 to 7.51) and relaparotomy (RR 3.84; 95%CI 1.28 to 1.49). The median of length of PICU stay was 4 days longer in children with pre-operative serum albumin levels ≤ 3.00 g/dL (P<0.001). Conclusions Hypoalbuminemia condition in children undergo abdominal surgery is associated with increased risk of post-operative sepsis, longer length of stay in PICU, and risk of relaparotomy.